Mechanically-milled YBaCo4O7+ for oxygen sorbents: insights into oxygen contamination and surface structure - So, Byoungjin; Hong, Seok-Min; Lee, Chang Hwa (Nuclear engineering and technology, 2025)
We report on the ball-milling effect and surface structure of YBaCo4O7+δ, which is being considered for use as oxygen sorbents through grazing incidence x-ray diffraction and X-ray photoelectron spectroscopy. Morphologies from unmilled powders were compared to morphologies of powders that had been milled for 2 or 20 h. Milling decreased the transition temperature for oxygen intake and release and caused residual strain-induced transition were accompanied. After excess oxygen was incorporated, the less ordered structure at shallow depth was found in both milled and unmilled specimens. The results could help to understand how ball-milling of the YBaCo4O7+δ affects its structures and oxygen-storage properties KCI Citation Count: 0